2017
DOI: 10.1177/1556264617743834
|View full text |Cite
|
Sign up to set email alerts
|

In Defense of the Questionable: Defining the Basis of Research Scientists’ Engagement in Questionable Research Practices

Abstract: National Institutes of Health principal investigators reported their perceptions of the ethical defensibility, prevalence in their field, and their personal willingness to engage in questionable research practices (QRPs). Using ethical defensibility ratings, an exploratory factor analysis yielded a two-factor solution: behaviors considered unambiguously ethically indefensible and behaviors whose ethical defensibility was more ambiguous. In addition, increasing perceptions that QRPs affect science predicted red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 40 publications
0
26
0
Order By: Relevance
“…Each scale was an aggregation of the 15 items, with higher scores indicating greater endorsement of QRPs. The items demonstrated acceptable reliability, suggesting that participants were responding to each item similarly as in previously validated studies (Cronbach’s α s > 0.80) [45].…”
Section: Methodsmentioning
confidence: 65%
See 2 more Smart Citations
“…Each scale was an aggregation of the 15 items, with higher scores indicating greater endorsement of QRPs. The items demonstrated acceptable reliability, suggesting that participants were responding to each item similarly as in previously validated studies (Cronbach’s α s > 0.80) [45].…”
Section: Methodsmentioning
confidence: 65%
“…Previous research has additionally indicated that overall experience in one’s field is especially predictive of engagement in QRPs. That is, early-career researchers appear more prone to QRP endorsement when not focused on consistency between their research identities and research ideals [45]. Perhaps early-career researchers are aggressive in a way that gives them a greater propensity for marginally ethics behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This literature has also developed an inventory of 'novel' forms of academic misbehaviour (Callaway 2015;Sacco et al 2018;Biagioli et al 2019;Bouter et al 2016), including estimations of how often some of these forms occur (e.g. Hopp and Hoover 2017;Fanelli 2009).…”
Section: Literaturementioning
confidence: 99%
“…However, psychological scientists have recently confronted their questionable research practices (John, Loewenstein, & Prelec, 2012), many of which arise during the writing (or revising) process (Sacco, Bruton, & Brown, 2018). Questionable research practices include…”
mentioning
confidence: 99%